An experimental study on the heat transfer performance of a loop heat pipe system with ethanol-water mixture as working fluid for aircraft anti-icing. (August 2019) - Su, Qian; Chang, Shinan; Song, Mengjie; Zhao, Yuanyuan; Dang, Chaobin
Highlights: Ethanol-water mixture was used in a loop heat pipe for aircraft anti-icing. The loop heat pipe with ethanol-water mixture obtained better performance. Phase-change inhibition explains the better performance of the system with mixture. 60% concentration of mixture reduced response time of the system to 60.16 min. 60% concentration of mixture enabled the highest temperature distribution on wing. Abstract: Owing to the increasing demand of an energy-saving aircraft anti-icing technology and cooling of hydraulic system, loop heat pipes are gradually becoming efficient heat transfer mediums that can meet both anti-icing and heat dissipation requirements. To fundamentally investigate the heat transfer performance of a loop heat pipe used for aircraft anti-icing, a stainless steel-nickel one was fabricated and tested at three typical inclination angles under both steady and transient states, with the system performance as the final evaluation index. Additionally, to address the freezing problem under negative temperature flight conditions, ethanol-water mixture with four concentrations was specially used as the working fluid. The steady-state results showed that, 60% concentration of mixture enabled the loop heat pipe to obtain a lower operating temperature as 178.1 °C, and a smaller thermal resistance as 0.26 °C/W at 300 W. In transient tests, the loop heat pipe with 60% concentration of mixture operated robustly and stably, and reduced the total response time by 30.18%, about 26 mins, than in pure ethanol group. It also achieved the highest temperature distributions on the wing at −20°, which were about 31.8 °C higher than those in pure ethanol group. This study aims to effectively guide the utilization of ethanol-water mixture in loop heat pipes, and shows highly practical value in further applications of loop heat pipes in aircraft anti-icing.